Hantavirus : Ancaman Zoonosis sebagai penyebab penyakit Infeksi Emerging - Husnun Amalia; Gladys Kusumowidagdo; Wawan Kurniawan (Jurnal Biomedika dan Kesehatan, 2026)
Hantavirus is a zoonotic virus belonging to the genus Orthohantavirus which causes emerging infectious diseases with high levels of morbidity and mortality. This virus is transmitted primarily through exposure to aerosols containing urine, feces, or saliva of infected rodents. Climate change, urbanization, changes in land use, and increasing interactions between humans and reservoirs contribute to the increasing risk of hantavirus transmission in various regions, including Indonesia. Hantaviruses are divided into Old World hantaviruses which cause Hemorrhagic Fever with Renal Syndrome (HFRS) and New World hantaviruses which cause Hantavirus Cardiopulmonary Syndrome (HCPS). Clinical manifestations vary from acute fever to renal or respiratory failure with a fatality rate that can reach 30–50% in HCPS. Diagnosis is made through a combination of history, clinical manifestations, serological examination, and molecular detection using RT-PCR. Until now, there is no specific antiviral or vaccine available that is widely used, so management still focuses on supportive therapy. In Indonesia, hantavirus infections are thought to still be underdiagnosed and underreported, even though serological and molecular evidence shows the circulation of the virus in humans and rodents. Hantavirus is an emerging zoonotic disease that has the potential to become a threat to public health. Increasing clinical awareness, strengthening surveillance, early detection, rodent control, and implementing the One Health approach are important strategies to reduce the risk of disease transmission and impact, especially in developing countries like Indonesia.